PREDICTION SUSTAINABILITY COMPANY USING ARTIFICIAL NEURAL NETWORK - Rifa, Rizka Noor; Muslih, Muhamad (RIMA - Research In Management and Accounting, 2018)
The study aims to find out how to predict company sustainability using Artificial Neural Networks (ANN) and looks at the relationship of board tenure, board age, company size, profitability, leverage, and liquidity in predicting sustainability of Asia Sustainability Reporting Rating (ASRR) participants in Indonesia period 2009-2018. Previous studies state that ANN is considered to provide accurate results in predictions. Therefore, this study uses ANN modeling for predicting sustainability. Company sustainability is assessed by analyzing sustainability performance in the Company’s Sustainability Report based on the Global Reporting Initiatives (GRI) G4 guidelines. The results of predictions using ANN indicate that company size, liquidity, and leverage contribute more than 50% in predicting company sustainability. Meanwhile, profitability, board age, and biard tenure contribute less than 50%.